A Pedagogy of Provocation: Teaching Troubling Women’s Studies - Bride, Kate (Atlantis)

(untitled) (Mount Saint Vincent University, 2012)
This article focuses on the 2004 publication, Troubling Women’s Studies: Pasts, Presents and Possibilities. In 2005, a colleague and I used Troubling Women’s Studies in our graduate feminist theory course, and this analysis highlights student responses to the book with a particular focus on epistemology, pedagogy and identity. My rationale for making the book central is that when students study Troubling Women’s Studies, they often confront their expectations of the discipline which has perhaps been idealized by them. Through questioning not only the power, but also the limitations, of foundational narratives in women’s studies, it is possible that one might undergo a loss of attachment (or at least a critical encounter with an attachment that may engender a loss). In this regard, I reflect upon how the work of teaching and learning Troubling Women's Studies produces such losses and can be productive for re-animating the field.